Phosphoglycerate dehydrogenase stabilizes protein kinase C delta type mRNA to promote hepatocellular carcinoma progression - Bin Cheng; Pai Peng; Shi Chen; Rui Liu; Xiaosong Li; Ke Wang; Jing Ma; Kai Wang; Ni Tang; Ailong Huang (Signal Transduction and Targeted Therapy)
Abstract Metabolic reprogramming not only reshapes cellular bioenergetics but also profoundly influences RNA metabolism through metabolite signaling and the RNA-binding activities of metabolic enzymes. Emerging evidence highlights that certain metabolic enzymes act as RNA-binding proteins (RBPs) to regulate gene expression and promote tumor progression. However, the non-catalytic post-transcriptional regulatory functions of metabolic enzymes in hepatocellular carcinoma (HCC) remain largely unexplored. In this study, we performed RNA-protein interactome profiling to identify potential non-canonical RBPs in HCC cells and established phosphoglycerate dehydrogenase (PHGDH) as a functional RBP. We further uncovered a previously unrecognized RNA-binding domain in PHGDH that directly binds cellular mRNAs and plays a key role in HCC cell proliferation. Mechanistically, PHGDH bound directly to the 3’untranslated region (3’UTR) of protein kinase C delta type (PRKCD) mRNA via its RNA-binding domain, thereby stabilizing the transcript and elevating PRKCD protein levels. PHGDH-dependent PRKCD upregulation promoted HCC progression by inducing mitophagy and inhibiting apoptosis. Additionally, decoy oligonucleotides that specifically block the RNA-binding activity of PHGDH markedly impaired its regulation of target genes and suppress HCC cell proliferation. Combination therapy using decoy oligonucleotides or the PRKCD inhibitor sotrastaurin with sorafenib synergistically inhibited HCC progression. Collectively, our findings reveal a non-canonical role of PHGDH in regulating mRNA metabolism and modulating mitophagy. Targeting the RNA-binding activity of PHGDH with decoy oligonucleotides represents a promising therapeutic strategy for HCC.